Peripheral blood mononuclear cells (PBMC) microbiome is not affected by colon microbiota in healthy goats - Ainize Peña-Cearra; Alejandro Belanche; Monika Gonzalez-Lopez; José Luis Lavín; Miguel Ángel Pascual-Itoiz; Elisabeth Jiménez; Héctor Rodríguez; Ana Mª. Aransay; Juan Anguita; David R. Yáñez-Ruiz; Leticia Abecia (Animal Microbiome, 2021)
Abstract Background The knowledge about blood circulating microbiome and its functional relevance in healthy individuals remains limited. An assessment of changes in the circulating microbiome was performed by sequencing peripheral blood mononuclear cells (PBMC) bacterial DNA from goats supplemented or not in early life with rumen liquid transplantation. Results Most of the bacterial DNA associated to PBMC was identified predominantly as Proteobacteria (55%) followed by Firmicutes (24%), Bacteroidetes (11%) and Actinobacteria (8%). The predominant genera found in PBMC samples were Pseudomonas, Prevotella, Sphingomonas, Acinetobacter, Corynebacterium and Ruminococcus. Other genera such as Butyrivibrivio, Bifidobacterium, Dorea and Coprococcus were also present in lower proportions. Several species known as blood pathogens or others involved in gut homeostasis such as Faecalibacterium prausnitzii were also identified. However, the PBMC microbiome phylum composition differed from that in the colon of goats (P ≤ 0.001), where Firmicutes was the predominant phylum (83%). Although, rumen liquid administration in early-life altered bacterial community structure and increased Tlr5 expression (P = 0.020) in colon pointing to higher bacterial translocation, less than 8% of OTUs in colon were also observed in PBMCs. Conclusions Data suggest that in physiological conditions, PBMC microbiome differs from and is not affected by colon gut microbiota in small ruminants. Although, further studies with larger number of animals and covering other animal tissues are required, results point to a common circulating bacterial profile on mammals being phylum Proteobacteria, and genera Pseudomonas and Prevotella the most abundants. All suggest that PBMC microbiome in healthy ruminants could be implicated in homeostatic condition. This study expands our knowledge about PBMC microbiome contribution to health in farm animals.